Mord(s)bilder - Aufzählungen von Gewalt bei Seneca und Lucan - Backhaus, Maria (Millennium-Studien / Millennium Studies, 2019)
Often noticed, frequently criticized, the descriptions of physical violence in Seneca's philosophical work De ira and Lucan's civil war epic De bello civili irritate until today. Only looking at the theory of rhetoric, the use of exempla and the staging of violence allows an approach to ancient reception attitudes and reveals the connections between enumeration and visualizability, violence and the the arousal of the emotions.